2003
DOI: 10.1097/01.brs.0000048666.17934.17
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Anterior Spinal Instrumentation and Allograft Fibula for the Treatment of Pott Disease

Abstract: The use of anterior spinal stabilization accompanied with a structural allograft fibula is effective after proper radical débridement for interbody fusion, deformity correction, and maintenance in cases of multisegment-involved Pott disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 25 publications
2
40
1
2
Order By: Relevance
“…The retroperitoneal approach requires careful protection of the ureter, lumbosacral plexus, and sympathetic chain [34]. Similar series have reported on major vascular injuries [35], deep venous thrombosis [11,36], pneumothorax, haemothorax, atelectasis and pneumonia [11,36,37], urinary tract infections [11], secondary non-specific infection [36][37][38] occasionally necessitating re-debridement and implant removal [35], hardware failure or breakage [12,38], and death due to pulmonary insufficiency [11,38].…”
Section: Discussionmentioning
confidence: 97%
“…The retroperitoneal approach requires careful protection of the ureter, lumbosacral plexus, and sympathetic chain [34]. Similar series have reported on major vascular injuries [35], deep venous thrombosis [11,36], pneumothorax, haemothorax, atelectasis and pneumonia [11,36,37], urinary tract infections [11], secondary non-specific infection [36][37][38] occasionally necessitating re-debridement and implant removal [35], hardware failure or breakage [12,38], and death due to pulmonary insufficiency [11,38].…”
Section: Discussionmentioning
confidence: 97%
“…Anterior debridement and arthrodesis allow reaching the focal point of the disease directly, effective debridement of the focal point, rapid bony union with the grafts and prevent progressive collapse and kyphosis [12,20,21,30,32]. However, it has been reported that such successful outcomes are not observed regarding progressive collapse and kyphosis, particularly in the case of two or more levels of involvement, risks of graft insufficiency and increased kyphotic deformity [1,3,9,11,15,23,25]. Moon et al stated that interbody fusion performed with classical anterior radical surgery per se in ineffective in the correction of kyphosis.…”
Section: Discussionmentioning
confidence: 99%
“…The kyphotic correction and cord decompression achieved by radical anterior intervention as described by Hodgson and Stock may be under risk with the collapses, breaks or insufficiency problems that may result resorption in the grafts used [12,22,26,29]. The reinforcement of correction performed in kyphotic deformity with posterior or anterior instrumentation prevents the collapse or breakdown of the graft, decreases pseudoarthrosis rate, and allows early ambulation and rehabilitation [1,2,6,9,12,15,16,22,25,26,29,31,33].…”
Section: Introductionmentioning
confidence: 99%
“…Oga et al in 1993 demonstrated that bio-film formation and adherence of mycobacterium tuberculosis to the metallic implants is negligible making them susceptible to host defence mechanism and anti-tuberculous drugs [14]. Their findings removed the phobia of using instrumentation in active spinal tuberculosis [14,15] leading many surgeons to use instrumentation posteriorly in addition to the anterior procedure [16][17][18][19][20] or anteriorly [21][22][23][24] with good results.…”
Section: Surgery In Active Diseasementioning
confidence: 99%